2006
DOI: 10.1210/me.2005-0351
|View full text |Cite
|
Sign up to set email alerts
|

Stress Kinase Signaling Regulates Androgen Receptor Phosphorylation, Transcription, and Localization

Abstract: Activation of signal transduction kinase cascades is known to alter androgen receptor (AR) activity, but the molecular mechanisms are still poorly defined. Here we show that stress kinase signaling regulates Ser 650 phosphorylation and AR nuclear export. In LNCaP prostate cancer cells, activation of either MAPK kinase (MKK) 4:c-Jun N-terminal kinase (JNK) or MKK6:p38 signaling pathways increased Ser 650 phosphorylation, whereas pharmacologic inhibition of JNK or p38 signaling led to a reduction of AR Ser 650 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 40 publications
8
155
0
Order By: Relevance
“…Similar to the case of p53, both p38 and JNK can phosphorylate the androgen receptor (AR) at Ser650 and promote its nuclear export in prostate cancer cells thereby reducing AR-mediated transcription (Gioeli et al, 2006). It was also demonstrated that decreasing MKK4 or MKK6 expression levels by siRNA led to increased AR nuclear accumulation and transactivation.…”
Section: Role Of P38 In Cancermentioning
confidence: 90%
See 1 more Smart Citation
“…Similar to the case of p53, both p38 and JNK can phosphorylate the androgen receptor (AR) at Ser650 and promote its nuclear export in prostate cancer cells thereby reducing AR-mediated transcription (Gioeli et al, 2006). It was also demonstrated that decreasing MKK4 or MKK6 expression levels by siRNA led to increased AR nuclear accumulation and transactivation.…”
Section: Role Of P38 In Cancermentioning
confidence: 90%
“…It was also demonstrated that decreasing MKK4 or MKK6 expression levels by siRNA led to increased AR nuclear accumulation and transactivation. (Gioeli et al, 2006). As the AR plays a key role in the progression of prostate cancer, then loss of function mutants of MKK4 may hypersensitize the AR to androgen and promote the androgen-independent diseased state.…”
Section: Role Of P38 In Cancermentioning
confidence: 99%
“…However, as in the case of Akt, other authors reported that GSK3β is required for AR gene expression [44]. The phosphorylation of Ser650 is also upregulated by stress kinase signalling and reduces AR transcription by augmentation of AR export to the cytoplasm [45]. So far, it has not been established which AR amino acid sequence is a target for Mdm2-driven ubiquitylation.…”
Section: Ligand-independent Proteasomal Degradation Of Armentioning
confidence: 99%
“…Various studies have shown the role of glycogen synthase kinase 3b (GSK3b), stress kinase, mammalian target of rapamycin (mTOR) kinase and cyclin-dependent kinase 1 in regulating phosphorylation, stability and localization of AR (Wang et al, 2004;Cinar et al, 2005;Chen et al, 2006;Gioeli et al, 2006). Further, there are numerous studies suggesting the importance of Akt/PKB (a serine/threonine kinase) activation in AR degradation (Lin et al, 2001(Lin et al, , 2002Liao et al, 2005) as well as AR activation (Miyamoto et al, 2005;Reddy et al, 2006); though the interaction of Akt with AR largely remains unclear.…”
Section: Introductionmentioning
confidence: 99%